Pasca Panen dan Saluran Pemasaran Ikan Guppy (Studi Kasus di Peternakan Ikan Guppy Kecamatan Pare Kabupaten Kediri) - Ida Bagus Hidayatullah; Endro Puji Astoko; Heru Setiyadi (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
The objective of this study was to determine the post-harvest process for guppy fish and the marketing channels at Mr. Mauludy's farm in Pare District, Kediri Regency. The study was conducted from February 2026 to April 2026, using a purposive sampling technique. The results of this study are that post-harvest activities of guppy fish include several stages, namely harvesting, sorting and grading, temporary storage, packaging, and distribution and marketing. These stages are carried out to maintain the quality of guppy fish so that they remain in healthy condition so that they have a good selling value when marketed. In its implementation, post-harvest activities still face several obstacles such as poorly controlled water cleanliness, failure of fish to adapt after harvest, excessive feeding, and the presence of cannibalistic behavior in guppy fish which can cause losses for farmers. The marketing channels for guppy fish in this study consist of two channels: direct marketing channels from producers to consumers and first-level marketing channels from producers to collectors and then to consumers. The selling price of guppy fish to collectors tends to be lower than direct sales to consumers due to the profit margin taken by collectors.